2014
DOI: 10.15560/10.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Fish larvae from the Gulf of California to Colima, Mexico: an update

Abstract: An updated taxonomic list of marine fish larvae from the Gulf of California to Colima, Mexico is presented. A total of 579 taxa belonging to 119 families, 256 genera, and 423 species were recorded. The list was compiled using 14 publications on fish larvae research (1974-2012), and the fish larvae identified from 315 samples collected with Bongo nets during 10 oceanographic cruises made from the Gulf of California to Bahía de Banderas, Mexico, from 2003 to 2007 (this study). The most important families in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the present study we attempted, from a modest sample size, identify as precise as possible most of the zooplankton assemblage of the tropical Islas Marías Archipelago. As a region not previously studied we found a large proportion of fish larvae not previously observed at ichthyoplanktonic surveys done along the west coast of Baja California Peninsula, Gulf of California, or Cape Corrientes regions during the more three decades of research (1980 to 2014) (Aceves-Medina et al, 2003, 2004Franco-Gordo et al, 1999, 2004Aceves-Medina et al, 2003, 2004Funes-Rodríguez et al, 2011;SilvaSegundo et al, 2008;León-Chávez et al, 2010;FunesRodríguez et al, 2011;Avendaño-Ibarra et al, 2013, 2014. These are most likely fish larvae of benthic or demersal coastal fish species, which larval description and taxonomy is still highly fragmented (Brogan, 1992;Moser, 1996).…”
Section: Potential Methodological Biasesmentioning
confidence: 48%
See 1 more Smart Citation
“…In the present study we attempted, from a modest sample size, identify as precise as possible most of the zooplankton assemblage of the tropical Islas Marías Archipelago. As a region not previously studied we found a large proportion of fish larvae not previously observed at ichthyoplanktonic surveys done along the west coast of Baja California Peninsula, Gulf of California, or Cape Corrientes regions during the more three decades of research (1980 to 2014) (Aceves-Medina et al, 2003, 2004Franco-Gordo et al, 1999, 2004Aceves-Medina et al, 2003, 2004Funes-Rodríguez et al, 2011;SilvaSegundo et al, 2008;León-Chávez et al, 2010;FunesRodríguez et al, 2011;Avendaño-Ibarra et al, 2013, 2014. These are most likely fish larvae of benthic or demersal coastal fish species, which larval description and taxonomy is still highly fragmented (Brogan, 1992;Moser, 1996).…”
Section: Potential Methodological Biasesmentioning
confidence: 48%
“…Offshore zooplankton assemblages from the mouth of the Gulf of California and coastal Cape Corrientes region have been studied focused only on specific taxonomic groups, such as Copepoda (Chen, 1986;Jiménez-Pérez & Lara-Lara, 1988;Hernández-Trujillo & Esquivel-Herrera, 1989;Gómez-Gutiérrez & Hernández-Trujillo, 1994;López-Ibarra, 2008;Palomares-García et al, 2013), Euphausiacea (krill) (Mundhenke, 1969;Brinton, 1979;Brinton & Townsend, 1980;Gómez-Gutiérrez & Hernández-Trujillo, 1994;Färber-Lorda et al, 2010;Ambríz-Arreola et al, 2012), Amphipoda (Siegel-Causey, 1982;Gasca & Franco-Gordo, 2008;Gasca et al, 2012), Mysidacea (Harrison & Bowman, 1987;Price, 2004), Decapoda larvae (Naranjo et al, 2006), Chaetognatha (Alvariño, 1963(Alvariño, , 1969RuizBoijseauneau et al, 2004), and ichthyoplankton (fish larvae) (Franco-Gordo et al, 1999, 2004Aceves-Medina et al, 2003, 2004Siordia-Cermeño et al, 2006;Silva-Segundo et al, 2008;Vilchis et al, 2009;León-Chávez et al, 2010, Avendaño-Ibarra et al, 2013, 2014. The rest of the zooplankton taxonomic groups are generally little known for Mexican waters (Brinton et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Within the GC, Alhstrom et al (1976) reported a presence of larvae of P. sio from the southern zone (south of the Archipelago zone); in addition, these authors report juvenile specimens in the ocean area ranging from 22°N near Colima, Mexico, down to 2°S around the Galapagos Islands. Aceves-Medina et al (2003) and Avendaño-Ibarra et al (2014) also reported the presence of P. sio larvae within the GC.…”
Section: Previous Distribution Rangementioning
confidence: 91%
“…A recent review of a taxonomic list generated from information provided by several research projects indicated the presence of 423 species (48.3% of 875 species recorded as adults in the GC) of fish larvae with descriptions of their morphology from the GC to the Colima coast (Avendaño‐Ibarra et al ., 2014). Most of the larval identification in the GC has been based on Moser (1996), who mostly depicted the diagnostic characteristics of fish larvae in the California Current region.…”
Section: Introductionmentioning
confidence: 99%
“…According to Moser (1996), in the Northeastern Pacific only larval morphological descriptions exist for Hoplopagrus guntherii Gill, 1862, Lutjanus argentiventris Peters, 1868, Lutjanus guttatus Steindachner, 1869, Lutjanus . novemfasciatus Gill, 1862, and Lutjanus peru Nichols & Murphy, 1922, which have been used for identifying lutjanid species larvae in the GC (Aceves‐Medina et al ., 2003; Avendaño‐Ibarra et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%